Healthcare resource allocation in the COVID-19 pandemic: Ethical considerations from the perspective of distributive justice within public health - Jeffrey Yuk-Chiu Yip (Elsevier, 2021)
Objectives: One of the many challenges public health practitioners have faced during the COVID-19 pandemic is deciding on the optimal allocation of limited healthcare resources. The current paper addresses the normative question of how medical resources can be optimally distributed during the current pandemic. Methods: As an article of short communication, an ethical analysis from the moral perspectives of distributive justice was conducted. Results: As multiple moral considerations must be analyzed to construct an ethically grounded and systematic allocation system, conflicting notions regarding efficiency, equity, and distributive justice are considered. Several practical recommendations were derived by leveraging the values of utilitarian, egalitarian, and prioritarian approaches to the proposed normative question. Conclusions: Transparent, equitable, and consistent allocation mechanisms underpinned by the ethical values and recommendations presented in this paper should inform prioritization guidelines when medical resources are stretched.